THE IMPACT OF REINTEGRATION INTO THE PROFESSIONAL ENVIRONMENT AFTER PARENTAL LEAVE ON THE PERFORMANCE OF EMPLOYEES IN THE PRIVATE SECTOR IN ROMANIA - Loredana Simona CARP (BERTA) (Challenges of the Knowledge Society)
Ensuring performance at work for people returning from parental leave is an important and sensitive topic for both employees and employers. Reintegrating into work after an extended absence can be challenging, but there are strategies and practices that can facilitate this process. The topic of this research is particularly relevant in the current context, given the importance of increasing the balance between personal and professional life of employees and ensuring an efficient reintegration into the work environment after a break period. Human resources motivation is a fundamental aspect for any organisation, as it is proven that motivated employees are more engaged and have higher productivity at work. Employees who return to work after a period of absence may be exposed to a series of challenges, such as adapting to changes in the work environment, finding a balance between parenting and professional responsibilities and further resuming the previous work rhythm. It is therefore essential to identify how HR motivation can be supported and encouraged at this stage. Positive intelligence is, in fact, the ability to identify opportunities and solutions, and to have a positive attitude in the face of challenges. The results of this research are intended to be transformed into valuable information for both managers and human resources professionals, but also for employees who return to work after the end of parental leave. By understanding this reintegration process more deeply and identifying effective practices, organisations can create a more supportive work environment and support employees in achieving professional and personal success.